An examination of Child and Adolescent Mental Health Services for Māori rangatahi [youth]. Issue 1 (2nd January 2016) - McClintock, Kahu; Tauroa, Roimata; Mellsop, Graham
Abstract : This article offers a review of the literature illustrating factors that can contribute to responsive Child and Adolescent Mental Health Services (CAMHS) for Māori (indigenous population of Aotearoa/New Zealand) rangatahi [12–19-year-old youths]. The development of a relevant CAMHS rangatahi tool to capture rangatahi views is also discussed. Literature searches using the keywords 'Māori rangatahi', 'Māori health', 'mental health', 'mental health services', 'adolescent health', 'child health' and 'youth services' were undertaken using the Medline and Index New Zealand databases as well as Google Scholar. The search was restricted to journals, books, and reports published in English from 1990 to 2012. High unmet CAMHS need for ethnic minorities and indigenous populations has prompted investigations relevant to improving mental health service delivery. Cultural interventions and service user views have provided some guidance. Two tool developments in the international literature (the Youth Services Survey – Families and, nationally, the Te Tomokanga – Caregivers Perspectives) capture a number of these issues. However, there is still an absence of a CAMHS tool in Aotearoa that seeks the specific views of rangatahi . In conclusion, CAMHS research is important for improving practice and CAMHS efficacy. Development of a CAMHS tool that allows specific rangatahi feedback is relevant to service provision in Aotearoa and globally.